Киноведение и научно-популярные издания как факторы социальной институционализации артхаусного кинематографа - Коновалов, Александр Евгеньевич; Коновалов, Олександр Євгенович; Konovalov, Oleksandr Ie. (Східноєвропейський національний університет імені Лесі Українки, 2015)
В статье анализируются научно-популярные издания и академические дисциплины киноведения как факторы, способствующие становлению артхаусного кинематографа в качестве социокультурного феномена и осмыслению процессов зарождения социальных интеракций, направленных на выполнение артхаусным кинематографом функций средства массовой коммуникации и социального института. По результатам поискового исследования предлагается к рассмотрению новое осмысление факторов социальной институционализации «арт-синема», одними из которых являются научно-популярные издания и научная дисциплина киноведение. In the sociological study of cinema, there exist a number of approaches. The given article is aimed at identi-fication and consideration of factors contributing to the formation of art-house cinema as a social and cultural phenomenon from the perspective of institutional theory. As the art-house cinema is an indicator of acute socio-cultural issues and a guide to the transformation of the modern society, the relevance of this article is determined by its study. The results of investigation showed that for further analysis of the art-house cinema in terms of institutionalism it is necessary to determine the structure of the art cinema as a social institution as well as the stages of its institutionalization. Film studies, scientific and popular publications are both structural elements of the social institution of art-house cinema and a means of the process of its institutionalization, especially on the stages of creating formal and informal institutions that regulate its functioning and organization of the status-role-playing system. In series with the institution of festivals that contribute to the formation and development of art-house cinema in the context of its production and distribution, film studies and popular science publications can be considered as the factors that contributed to the academic and scientific understanding of the phenomenon of art cinema.
Film Studies and Popular Science as the Factors of Art Cinema Social Institutio-nalization
Keywords: киноведение; артхаусный кинематограф; социальные интеракции; научно-популярные издания; социокультурный феномен; массовые коммуникации; film studies; art cinema; social interactions; popular science; sociocultural phenomenon; mass communications